Comparison of Tooth and Arch Dimensions in Dental Crowding, Spacing, and Normal Dentition: A Cross-Sectional Study from a Tertiary Orthodontic Centre in Nepal - Shrestha, Natasha; Bhattarai, Anisha; Shahi, Swati Singh; Sharma, Shakti (Journal of Bharatpur Hospital, 2026)
BackgroundDental crowding and spacing are the most common malocclusions worldwide, arising from imbalance between mesiodistal tooth size and dental arch dimensions (TSALD), yet Nepalese comparative morphometric data are limited. This study aimed to compare MD tooth dimensions, arch perimeter, IC, IP, IM widths, arch depth, and TSALD across crowded, normal, and spaced dentitions in maxillary and mandibular arches MethodsThis cross-sectional study analyzed 138 pretreatment orthodontic casts (age 19-34 years) from College of Medical Science-Teaching Hospital, Nepal. Based on TSALD, samples were categorized into crowded (≤ −4 mm; n=22), normal (0 ± 3 mm; n=22), and spaced (≥ +4 mm; n=94). MD widths of all permanent teeth (excluding second and third molars) were measured using a digital Vernier caliper. Arch perimeter was assessed using a brass-wire method. One-way ANOVA with Tukey post-hoc tests was applied (α=0.05).ResultsTotal maxillary tooth material was highest in crowded cases (75.62 ± 5.46 mm) and lowest in spaced cases (69.52 ± 4.75 mm; p